Онтогенетичні стани солодцю голого (Glycyrrhiza glabra L.) в культурі на півдні України - Zakharenko, V.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The peculiarities of ontogenesis of seeds plants for Glycyrrhiza glabra L. in culture on the South of the Ukraine have been shown. The morphological descriptions and biometrical characteristics of seed plants on different development stage – from the shoots up to the transition of plant in generative condition – have been given.